Expropriation of real estate - key tool in achieving sustainable cities and communities - Leșan, Anna (Technium Social Sciences Journal, 2024)
This article presents an analysis of the issues related to the emergence of the need for expropriation of real estate as a principal instrument for the creation of sustainable cities and communities. Therefore, following the analysis, it can be concluded that with the signing of the Association Agreement with the European Union by the Republic of Moldova, it is necessary to develop the country according to European standards. Consequently, an important component of the Sustainable Development Objective is the development of infrastructure. The development of infrastructure inevitably entails the expropriation of real estate for the construction of technical and public utilities, as well as road networks. The quality of road infrastructure, the quality of water supply, and the quality of electricity supply at the international level were subjected to analysis. Given that all infrastructure development projects are financed with foreign funds, an analysis was conducted of the volume of investments allocated by the European Bank for Reconstruction and Development (EBRD) and their distribution. In order to gain insight into the current state of affairs in Moldova, an investigation was conducted into the provision of technical building infrastructure elements by the country's development regions. It was found that, at this time, investments are required for infrastructure development, as a significant proportion of localities lack the necessary water supply and sewerage networks, as well as natural gas (see Table 1). It thus follows that the principal instrument for achieving these objectives is the expropriation of real estate for public utility.